Overexpression of microRNA-96-5p inhibits autophagy and apoptosis and enhances the proliferation, migration and invasiveness of human breast cancer cells - Shi, Yawei (Oncol Lett, 2017)
MicroRNAs (miRNA/miR) are short non-coding RNAs that function in the endogenous regulation of genes. miRNAs serve important roles in cellular events such as apoptosis, cell proliferation, migration, invasion, autophagy and the cell cycle. They also control the genesis and progression of tumors. Autophagy is a self-digestive process that occurs as a response to stress, and serves two opposite roles in tumor promotion or inhibition that may result in resistance to therapy. A number of studies have revealed that miRNAs control autophagic activity by targeting autophagy-associated genes, particularly in cancer. These previous studies demonstrated that miR-96-5p is upregulated in several types of malignant tumors. However, other functions of miR-96-5p in breast cancer, particularly those that are associated with autophagy, remain unknown. miR-96-5p expression was demonstrated to be upregulated in breast cancer cells compared with in normal breast epithelial cells. The overexpression of miR-96-5p inhibited autophagy, particularly starvation-induced autophagy, in MCF-7 and MDA-MB-231 cells. In addition, this inhibitory effect may have resulted in the suppression of Forkhead box O1. Additionally, the overexpression of miR-96-5p may promote cell proliferation, migration and invasion and inhibit apoptosis in MCF-7 and MDA-MB-231 cells. These data indicate that miR-96-5p is involved in the progression of breast cancer cells and may represent a potential therapeutic target for the treatment of breast cancer.